Power in preaching - Lim, Johnson T.K (Singapore Word and Works, 2005)
To preach the Word of God boringly, lifelessly or indifferently is a travesty of biblical preaching. Contemporary preaching appears powerless because the preacher is unctionless. For preaching to transform lives and not merely to transmit knowledge, preachers need the unction of the Holy Spirit.
Keywords: Preaching